Multi‐Functional 2D Covalent Organic Frameworks with Diketopyrrolopyrrole as Electron Acceptor - Luo, Liang; Li, Chunbin; Wang, Yuancheng; Chen, Pinyu; Zhou, Zhaoqiong; Chen, Tianwen; Wu, Kunlan; Ding, San‐Yuan; Tan, Luxi; Wang, Jianguo; Shao, Xiangfeng; Liu, Zitong (Small (Weinheim an der Bergstrasse, Germany), 2024)
2D covalent organic framework (COF) materials with extended conjugated structure and periodic columnar π‐arrays exhibit promising applications in organic optoelectronics. However, there is a scarcity of reports on optoelectronic COFs, mainly due to the lack of suitable π‐skeletons. Here, two multi‐functional optoelectronic 2D COFs DPP‐TPP‐COF and DPP‐TBB‐COF are constructed with diketopyrrolopyrrole as electron acceptor (A), and 1,3,6,8‐tetraphenylpyrene and 1,3,5‐triphenylbenzene as electron donor (D) through imine bonds. Both 2D COFs showed good crystallinities and AA stacking with a rhombic framework for DPP‐TPP‐COF and hexagonal one for DPP‐TBB‐COF, respectively. The electron D–A and ordered intermolecular packing structures endow the COFs with broad UV–vis absorptions and narrow bandgaps along with suitable HOMO/LUMO energy levels, resulting in multi‐functional optoelectronic properties, including photothermal conversion, supercapacitor property, and ambipolar semiconducting behavior. Among them, DPP‐TPP‐COF exhibits a high photothermal conversion efficiency of 47% under 660 nm laser irradiation, while DPP‐TBB‐COF exhibits superior specific capacitance of 384 F g−1. Moreover, P‐type doping and N‐type doping are achieved by iodine and tetrakis(dimethylamino)ethylene on a single host COF, resulting in ambipolar semiconducting behavior. These results provide a paradigm for the application of multi‐functional optoelectronic COF materials. By rationally designing a donor–accepter (D–A) system and utilizing diketopyrrolopyrrole (DPP) as an electron acceptor, two multi‐functional optoelectronic 2D covalent organic frameworks (COFs) are obtained with photothermal conversion, supercapacitor property, and ambipolar semiconducting behavior.